1984
DOI: 10.1111/j.1432-1033.1984.tb08530.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of collagenase and collagenase inhibitors by osteoblast-like cells in culture

Abstract: A rat osteosarcoma cell clone (ROS 17/2), and osteoblast-enriched populations from rat calvaria cultured in the presence of concanavalin A, have been shown to produce latent collagenase and collagenase inhibitors. The enzymes and inhibitor activities from the ROS 17/2 cells were concentrated by ammonium sulphate precipitation and separated by gel filtration on AcA 54 resin. The size of the latent collagenase (Mr z 58000) was reduced on conversion to active enzyme ( M , ~448000) by p-aminophenylmercuric acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(34 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…This constitutive MMP-1 seems to serve as a remodeling element of connective tissue under physiological conditions 27) . Otsuka et al also demonstrated that rat osteosarcoma cell line produced collagenolytic enzymes 23) . MMP-1 mRNA was highly expressed in this study after 48 h stimulated with Prevotella nigrescens LPS, and the increase was dosedependent.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This constitutive MMP-1 seems to serve as a remodeling element of connective tissue under physiological conditions 27) . Otsuka et al also demonstrated that rat osteosarcoma cell line produced collagenolytic enzymes 23) . MMP-1 mRNA was highly expressed in this study after 48 h stimulated with Prevotella nigrescens LPS, and the increase was dosedependent.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In this study, TIMP-1 was expressed by MG-63 osteoblastic cells. Otsuka 23) , Johansen 32) , Uchida 33) . also reported that osteoblastic cells synthesized TIMP-1.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 This protease is also secreted by osteoclasts in sub-osteoclastic zones at sites of bone resorption. 18,29,30 Despite the numerous studies undertaken on osteoblast/biomaterial interactions, the regulation of their proteolytic activity and ECM remodeling remains to be understood. Furthermore, little is known on the influence of biomaterials such as titanium or ceramics on the expression and synthesis of MMPs and TIMPs by human osteoblastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The production of MMPs by bone cells in in vivo and in vitro investigations suggests their importance in bone remodeling. 18,29 In this process, collagenases producing osteoblasts have a major role by degrading the osteoid layer, exposing the underlying mineralized matrix to osteoclastic activity. 12,30 Osteoblasts produce collagenase in response to 1,25(OH) 2 vitamin D 3 or interleukin-1 stimulation.…”
Section: Introductionmentioning
confidence: 99%